3 Degrees More The Impending Hot Season and How Nature Can Help Us Prevent It - Wiegandt, Klaus; SpringerLink (Online service) (Cham : Springer Nature Switzerland : Imprint: Springer, 2024)
This open access book describes in detail what life on this planet would be like if its average surface temperature were to rise 3 degrees Celsius above the preindustrial level. On this basis, the book argues that it is imperative to keep this temperature rise below 2 degrees Celsius. It then lays out a detailed plan of what politically feasible, cost-effective measures should now be taken to achieve this goal. In this context, the book provides detailed discussions of climate finance, climate education and nature-based solutions. The book has been translated into English from the original German version published in 2022, and contains an original foreword and preface.
Chapter 1 Climate and weather at 3 degrees more -- Chapter 2 Biodiversity at the tipping point -- Chapter 3 Agriculture in a hot world -- Chapter 4 Escape from heat, drought and extreme weather -- Chapter 5 Economic impacts -- Chapter 6 Stop rainforest deforestation -- Chapter 7 Reforestation in the tropics and subtropics -- Chapter 8 Bauhaus Earth -- Chapter 9 Peatland must be wet -- Chapter 10 Humus enrichment of soils -- Chapter 11 Strengthen terrestrial water cycles -- Chapter 12 Germany under climate stress -- Chapter 13 People must know what they are in for!.
Accessibility summary: This PDF does not fully comply with PDF/UA standards, but does feature limited screen reader support, described non-text content (images, graphs), bookmarks for easy navigation and searchable, selectable text. Users of assistive technologies may experience difficulty navigating or interpreting content in this document. We recognize the importance of accessibility, and we welcome queries about accessibility for any of our products. If you have a question or an access need, please get in touch with us at accessibilitysupport@springernature.com.
No reading system accessibility options actively disabled
Publisher contact for further accessibility information: accessibilitysupport@springernature.com
Keywords: Climatology; Environment; Environmental management; Climate Sciences; Environmental Sciences; Environmental Management